Influence of host planto n reproductive behavior of Leucoptera coffeella (Guérin-Meneville) (Lepidoptera: Lyonetiidae) - Fonseca, Marcy Das Graças; Lima, Eraldo Rodrigues; Araújo, Ana Paula Albano; Resende, Tiago Teixeira (Coffee Science - ISSN 1984-3909, 2013)
The objective of this study was to evaluate the effect of the host plant, Coffea arabica, the reproductive behaviorof Leucoptera coffeella. We evaluated: i) the effect of reproductive condition of females in response to the volatile coffee leaves, ii) the proportion of mating, start time and duration of copulation are affected by the presence of volatile coffee and iii) if femaleL. coffeella can lay eggs on another host. The assessment of olfactory response of virgin females and mated to the volatile coffee leaves was done using olfactometer “Y”. To evaluate the proportion of copulation, the start time and duration of copulation, couples were used in plastic cages with the presence or absence of volatiles of coffee leaves. And, to assess the ovoposition females were offered to them leaves of the host plant and not host. The volatiles emitted by host plant appeared to be not relevant to track their location by females, but these volatiles were important during mating. The proportion of mating, the onset and duration of copulation were significantly altered in the presence of volatile coffee. When a host plant was not offered to females as ovipositionsite, there was a considerable reduction in the number of eggs deposited, indicating that females use cues of the host plant to lay eggs. Thus, there was the host plant plays an important role in the reproductive behavior of L. coffeella.